Mismatch negativity at Fz in response to within-category changes of the vowel /i - Marklund, Ellen (Lippincott Williams & Wilkins, 2014)
The amplitude of the mismatch negativity response for acoustic within-category deviations in speech stimuli was investigated by presenting participants with different exemplars of the vowel /i/ in an odd-ball paradigm. The deviants differed from the standard either in terms of fundamental frequency, the first formant, or the second formant. Changes in fundamental frequency are generally more salient than changes in the first formant, which in turn are more salient than changes in the second formant. The mismatch negativity response was expected to reflect this with greater amplitude for more salient deviations. The fundamental frequency deviants did indeed result in greater amplitude than both first formant deviants and second formant deviants, but no difference was found between the first formant deviants and the second formant deviants. It is concluded that greater difference between standard and within-category deviants across different acoustic dimensions results in greater mismatch negativity amplitude, suggesting that the processing of linguistically irrelevant changes in speech sounds may be processed similar to nonspeech sound changes.